The Reception of Doris Lessing’s Novels in Franco’s Spain - Lázaro, Alberto (Atlantis. Journal of the Spanish Association for Anglo-American Studies, 2014)
Nobel Prize winner Doris Lessing’s serious concerns with political and social issues, as well as her constant experimentation with genre and style, have made her a highly prestigious literary figure in the English language. In Spain, her work was recognised in 2001 when she was awarded the Prince of Asturias Award for Letters. However, for years, some of her novels were practically unknown to Spanish readers. The first Spanish version of The Golden Notebook appeared in 1978, sixteen years after its publication in London. Why did it take so long? Did Spanish publishers ignore Lessing in the 1960s and 1970s? Did her controversial spirit clash with the traditional views of Franco’s censors? This article describes information found in censorship office files in an attempt to provide an explanation for the attitudes to Lessing’s novels in the Franco era. They contain valuable data regarding publisher and bookseller interest in Lessing at the time, with reference to Spanish and imported editions of her work, and, more importantly, provide some insight into the censors’ opinion of her fiction.